High-thermal-conductivity flexible bus and preparation method thereof

By designing the cladding structures of nanographene composite ceramic coating, silicone layer, aluminum alloy armor layer, multi-layer polyvinyl chloride layer and silicone grease coating on high-power laminated busbar, the copper outer covering layer is solved It is difficult to take into account the problem of heat dissipation, achieving efficient thermal management and power transmission safety.

CN119252534AInactive Publication Date: 2025-01-03YANG HUA KE CHUANG (SHEN ZHEN) XIN NENG YUAN ZHUANG BEI YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411547841.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The copper outer cladding of existing high-power laminated busbars is difficult to take into account the heat dissipation of the busbars, resulting in safety hazards in power transmission.

Method used

A highly thermally conductive flexible busbar is designed, and the cladding structure is adopted for nanographene composite ceramic coating, high thermally conductive silicone layer, aluminum alloy armor layer, multi-layer polyvinyl chloride layer and silicon grease coating. Through careful selection and Layered materials achieve excellent thermal conductivity and heat dissipation.

Benefits of technology

It improves the thermal management efficiency of the busbar, enhances its adaptability and durability in various environments, and ensures the reliability and efficiency of power transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252534A_ABST
    Figure CN119252534A_ABST
Patent Text Reader

Abstract

The invention discloses a high-thermal-conductivity flexible bus and a preparation method thereof, and relates to the technical field of power transmission. The high-thermal-conductivity flexible bus comprises a copper bar and a coating layer, and the coating layer sequentially comprises a first heat dissipation coating, a wrapping layer, a first polyvinyl chloride layer, an aluminum alloy armor layer, a second polyvinyl chloride layer and a second heat dissipation coating from inside to outside. The coating layer improves the thermal management efficiency of the bus, and enhances the adaptability and durability of the bus in various environments, thereby ensuring the reliability and efficiency of power transmission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of power transmission, and in particular to a high thermal conductivity flexible busbar and a preparation method thereof. Background Art

[0002] The laminated busbar of high-power converter has broad development prospects due to its excellent performance characteristics such as low inductance and easy installation. The high-power laminated busbar is stacked together in the form of thin and wide copper bars, and each layer is hot-pressed into one with very thin high-insulation strength materials. This overall high-power laminated busbar structure can withstand hundreds of kilograms of shear stress, and its conductive electrodes can withstand thousands of volts of voltage. In order to meet the performance requirements of high-power laminated busbars, its high-insulation strength material plays a vital role.

[0003] However, the high insulation strength materials of the copper busbar's outer covering are currently unable to take into account the heat dissipation of the busbar, which poses certain safety risks to power transmission. Summary of the invention

[0004] The present invention is made in view of the above-mentioned problems, and provides a high thermal conductivity flexible busbar and a preparation method thereof, aiming to solve the problem that the high insulation strength material of the outer coating of the current copper busbar is difficult to take into account the heat dissipation of the busbar, resulting in certain safety hazards in power transmission.

[0005] A first aspect of the present invention provides a high thermal conductivity flexible busbar, which includes a copper busbar and a coating layer, wherein the coating layer is, from inside to outside, a first heat dissipation coating, a wrapping layer, a first polyvinyl chloride layer, an aluminum alloy armor layer, a second polyvinyl chloride layer, and a second heat dissipation coating.

[0006] In some embodiments of the present invention, the first heat dissipation coating is a nano-graphene composite ceramic coating. The raw materials for preparing the nano-graphene composite ceramic coating include, by weight: 19 to 38 parts of thermal conductive heat dissipation powder, 0.1 to 3 parts of barium stearate dispersant, 0.1 to 0.2 parts of polyvinyl pyrrolidone, 12 to 15 parts of epoxy resin, 1 to 3 parts of polyether sulfone resin, and 1 to 5 parts of silane coupling agent.

[0007] In some embodiments of the present invention, the thermally conductive and heat dissipating powder includes, by weight: 2 to 5 parts of nano graphite powder, 6 to 10 parts of nano alumina powder, 1 to 5 parts of aluminum nitride powder, 5 to 10 parts of silicon dioxide powder, and 0.1 to 0.2 parts of silver powder.

[0008] In some embodiments of the present invention, the silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane or N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane.

[0009] In some embodiments of the present invention, the wrapping layer is a high thermal conductivity silicone layer, and the matrix of the silicone includes polydimethylsiloxane or polymethyltriethoxysilane.

[0010] In some embodiments of the present invention, the second heat dissipation coating is a silicone grease coating.

[0011] In some embodiments of the present invention, the thickness of the first heat dissipation layer is 0.5mm-1.5mm, the thickness of the wrapping layer is 0.5mm-2mm, the thickness of the first polyvinyl chloride layer is 0.5mm-1.5mm, the thickness of the aluminum alloy armor layer is 0.1mm-0.5mm, the thickness of the second polyvinyl chloride layer is 0.5mm-1.5mm, and the thickness of the second heat dissipation coating is 0.01mm-0.1mm.

[0012] A second aspect of the present invention provides a method for preparing a high thermal conductivity flexible busbar, comprising the following steps:

[0013] a: ultrasonically dispersing nano-graphite powder and polyvinyl pyrrolidone, adding the remaining thermal conductive and heat dissipating powder, barium stearate dispersant, and anhydrous ethanol, stirring, ultrasonically dispersing, vacuum drying, grinding, and filtering to obtain a first mixture;

[0014] b: kneading the epoxy resin, polyethersulfone resin and the first mixture for the first time, then adding the silane coupling agent for the second kneading, coating the kneaded product on the copper bus, baking and curing, to obtain a nano-graphene composite ceramic coating, i.e., the first heat dissipation coating;

[0015] c: a wrapping layer, a first polyvinyl chloride layer, an aluminum alloy armor layer, a second polyvinyl chloride layer, and a second heat dissipation coating layer are sequentially arranged on the surface of the first heat dissipation layer to obtain a high thermal conductivity flexible busbar.

[0016] In some embodiments of the present invention, in step a, the vacuum drying temperature is 70° C. to 85° C., and the grinding fineness is a particle size of less than or equal to 10 μm.

[0017] In some embodiments of the present invention, in step b, the temperature of the first banburying is 90°C to 110°C, the temperature of the second banburying is 110°C to 118°C, and the temperature of the baking is 280°C to 550°C.

[0018] The beneficial effects that can be achieved by the present invention are:

[0019] The present invention provides a high thermal conductivity flexible busbar. The coating design of the high thermal conductivity flexible busbar achieves excellent thermal conductivity and heat dissipation effects through carefully selected and layered materials. The innermost layer of nano-graphene composite ceramic coating uses the ultra-high thermal conductivity of graphene to quickly conduct heat; the high thermal conductivity silicone layer not only provides an additional heat conduction path, but also increases the flexibility and mechanical protection of the busbar; the aluminum alloy armor layer provides mechanical strength for the overall structure while enhancing electromagnetic compatibility; the two layers of polyvinyl chloride provide insulation and chemical corrosion resistance, and the outermost silicone grease coating further optimizes heat dissipation to ensure that heat is effectively transferred to the outside world. This series of materials work synergistically not only to improve the thermal management efficiency of the busbar, but also to enhance its adaptability and durability in various environments, thereby ensuring the reliability and efficiency of power transmission. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the cross-sectional structure of a busbar according to one embodiment of the present invention.

[0021] Description of reference numerals:

[0022] 1. Copper busbar; 2. First heat dissipation coating; 3. Wrapping layer; 4. First polyvinyl chloride layer; 5. Aluminum alloy armor layer; 6. Second polyvinyl chloride layer; 7. Second heat dissipation coating.

[0023] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0024] The accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present invention, and are not intended to limit the subject matter described in the claims.

[0025] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0026] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.

[0027] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0028] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0029] High-power laminated busbars are made of thin and wide copper bars stacked together, with thin layers of high-insulation-strength materials hot-pressed together. This overall high-power laminated busbar structure can withstand hundreds of kilograms of shear stress, and its conductive electrodes can withstand thousands of volts of voltage. In order to meet the performance requirements of high-power laminated busbars, its high-insulation-strength materials play a vital role. However, the high-insulation-strength materials of the copper bar outer coating are currently difficult to take into account the heat dissipation of the busbar, which poses certain safety risks to power transmission.

[0030] In view of this, the present invention proposes a high thermal conductivity flexible busbar, referring to Figure 1 The high thermal conductivity flexible busbar includes a copper busbar 1 and a coating layer, and the coating layer is sequentially from the inside to the outside: a first heat dissipation coating 2, a wrapping layer 3, a first polyvinyl chloride layer 4, an aluminum alloy armor layer 5, a second polyvinyl chloride layer 6, and a second heat dissipation coating 7.

[0031] The innermost first heat dissipation coating 2, i.e., the nano-graphene composite ceramic coating, utilizes the ultra-high thermal conductivity of graphene to quickly conduct heat; the wrapping layer 3, i.e., the high thermal conductivity silicone layer, not only provides an additional heat conduction pathway, but also increases the flexibility and mechanical protection of the busbar; the first polyvinyl chloride layer 4 serves as an insulating layer to avoid the risk of leakage and electric shock; the aluminum alloy armor layer 5 provides mechanical strength for the overall structure and enhances electromagnetic compatibility; the second polyvinyl chloride layer 6 serves as a sheath layer, which provides chemical corrosion resistance to prevent the busbar from being affected by external factors such as moisture and chemical corrosion; the outermost second heat dissipation coating 7 is a high thermal conductivity silicone grease coating, which further optimizes the heat dissipation and ensures that the heat is effectively transferred to the outside.

[0032] In this solution, the coating design of the high thermal conductivity flexible busbar achieves excellent thermal conductivity and heat dissipation through the careful selection and layered arrangement of materials. This series of materials work together to not only improve the thermal management efficiency of the busbar, but also enhance its adaptability and durability in various environments, thereby ensuring the reliability and efficiency of power transmission.

[0033] In some embodiments, the first polyvinyl chloride layer 4 is used as an insulating layer and uses SG-0 type polyvinyl chloride, and the second polyvinyl chloride layer 6 is used as a sheath layer and uses SG-4 type polyvinyl chloride. Due to the different relative molecular masses of different types of polyvinyl chloride, the van der Waals attraction or entanglement degree between PVC macromolecular chains changes accordingly, thereby obtaining different insulation, mechanical properties, heat resistance and weather resistance.

[0034] In some embodiments, the first heat dissipation coating 2 is a nano-graphene composite ceramic coating. The raw materials for preparing the nano-graphene composite ceramic coating include, by weight: 19 to 38 parts of thermal conductive heat dissipation powder, 0.1 to 3 parts of barium stearate dispersant, 0.1 to 0.2 parts of polyvinyl pyrrolidone, 12 to 15 parts of epoxy resin, 1 to 3 parts of polyether sulfone resin, and 1 to 5 parts of silane coupling agent.

[0035] In this solution, a high proportion of thermally conductive and heat-dissipating powder is used as the basis to provide an efficient heat conduction pathway, while the addition of barium stearate dispersant optimizes the dispersion of the powder, ensures the uniformity inside the coating, and thus reduces thermal resistance. Polyvinyl pyrrolidone, as a co-solvent, further improves the processing performance of the mixed liquid and makes the coating more uniform. The combination of appropriate amounts of epoxy resin and polyethersulfone resin not only enhances the bonding strength and chemical corrosion resistance of the coating, but also improves its mechanical strength and wear resistance. The use of silane coupling agent enhances the bonding force between the coating and the substrate, ensuring the long-lasting adhesion of the coating. Overall, this formula combines the synergistic effects of each component to create a nanographene composite ceramic coating with high thermal conductivity, excellent mechanical properties and good durability.

[0036] In some embodiments, the heat-conducting and heat-dissipating powder includes, by weight: 2 to 5 parts of nano-graphite powder, 6 to 10 parts of nano-alumina powder, 1 to 5 parts of aluminum nitride powder, 5 to 10 parts of silicon dioxide powder, and 0.1 to 0.2 parts of silver powder. The selection of the heat-conducting and heat-dissipating powder ensures high thermal conductivity, and at the same time has a large magnetic permeability, and has a strong interaction with the high-frequency electromagnetic waves when the busbar is used, so it has a high efficiency of absorbing waves, thereby improving the shielding effect of the present invention, and also taking into account the processing performance and structural stability of the material.

[0037] In some embodiments, the silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane or N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane. Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane.

[0038] In some embodiments, the wrapping layer 3 is a high thermal conductivity silicone layer, and the base of the silicone includes polydimethylsiloxane or polymethyltriethoxysilane. Polydimethylsiloxane or polymethyltriethoxysilane as a base material is more likely to interact with the resin component of the inner first heat dissipation layer 2 and the outer first polyvinyl chloride layer 4 interface to enhance the adhesion.

[0039] In some embodiments, the second heat dissipation coating 7 is a silicone grease coating. The silicone grease coating forms a synergistic effect with the inner high thermal conductivity silicone layer and the nano-graphene composite ceramic coating, improving the overall thermal conductivity of the coating layer, providing a faster and more effective way for heat conduction, reducing thermal boundary resistance and improving thermal conductivity.

[0040] In some embodiments, the thickness of the first heat dissipation layer 2 is 0.5 mm to 1.5 mm, the thickness of the wrapping layer 3 is 0.5 mm to 2 mm, the thickness of the first polyvinyl chloride layer 4 is 0.5 mm to 1.5 mm, the thickness of the aluminum alloy armor layer 5 is 0.1 mm to 0.5 mm, the thickness of the second polyvinyl chloride layer 6 is 0.5 mm to 1.5 mm, and the thickness of the second heat dissipation coating 7 is 0.01 mm to 0.1 mm. Controlling the thickness of each layer of the cladding layer within the above range can reduce costs while achieving excellent thermal conductivity and increase busbar flexibility.

[0041] A second aspect of the present invention provides a method for preparing a high thermal conductivity flexible busbar, comprising the following steps:

[0042] a: ultrasonically dispersing nano-graphite powder and polyvinyl pyrrolidone, adding the remaining thermal conductive and heat dissipating powder, barium stearate dispersant, and anhydrous ethanol, stirring, ultrasonically dispersing, vacuum drying, grinding, and filtering to obtain a first mixture;

[0043] b: kneading the epoxy resin, polyethersulfone resin and the first mixture for the first time, then adding the silane coupling agent for the second kneading, coating the kneaded product on the copper bus, baking and curing, to obtain a nano-graphene composite ceramic coating, i.e., the first heat dissipation coating;

[0044] c: a wrapping layer, a first polyvinyl chloride layer, an aluminum alloy armor layer, a second polyvinyl chloride layer, and a second heat dissipation coating layer are sequentially arranged on the surface of the first heat dissipation layer to obtain a high thermal conductivity flexible busbar.

[0045] It should be noted that the raw material ratio of the first heat dissipation coating in the preparation method is calculated by weight, including: 2 to 5 parts of nano graphite powder, 6 to 10 parts of nano alumina powder, 1 to 5 parts of aluminum nitride powder, 5 to 10 parts of silicon dioxide powder, 0.1 to 0.2 parts of silver powder, 0.1 to 3 parts of barium stearate dispersant, 0.1 to 0.2 parts of polyvinyl pyrrolidone, 12 to 15 parts of epoxy resin, 1 to 3 parts of polyether sulfone resin, and 1 to 5 parts of silane coupling agent. The wrapping layer is a high thermal conductivity silicone layer, and the second heat dissipation coating is a silicone grease coating.

[0046] In some embodiments, the arrangement of the first heat dissipation layer, the wrapping layer, the first polyvinyl chloride layer, the aluminum alloy armor layer, the second polyvinyl chloride layer and the second heat dissipation coating in step c can be achieved by known process methods in the industry, such as cold spraying technology, hot spraying technology, extrusion molding, drawing molding, printing and other methods.

[0047] In some embodiments, in step a, the vacuum drying temperature is 70° C. to 85° C., and the grinding fineness is a particle size of less than or equal to 10 μm.

[0048] In some embodiments, in step b, the temperature of the first kneading is 90°C to 110°C, the temperature of the second kneading is 110°C to 118°C, and the temperature of the baking is 280°C to 550°C.

[0049] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0050] Example 1

[0051] a. Ultrasonic dispersion of 3 parts of nano graphite powder and 0.1 parts of polyvinyl pyrrolidone, with the power of ultrasonic dispersion being 300W and the time being 30min, 8 parts of nano alumina powder, 2 parts of aluminum nitride powder, 10 parts of silicon dioxide powder, 0.1 parts of silver powder, and 1 part of barium stearate dispersant are added, stirring and ultrasonic dispersion are continued, and the amount of anhydrous ethanol added is 5wt% to 20wt% of the weight of the powder. Then vacuum drying at 80°C, ball milling using a ball mill for 3 to 6 hours, and filtering, so that the particle size is less than 10μm, to obtain the first mixture;

[0052] b. 12 parts of epoxy resin and 2 parts of polyethersulfone resin were first mixed with the first mixture, the mixing temperature was controlled at 90 ° C, the mixing time was 2 hours, and then 2 parts of γ-aminopropyl triethoxysilane were added to the mixed product for a second mixing at 115 ° C. After the mixing was completed, the product was coated on a copper bus and cured in an oven at 350 ° C.

[0053] c. A 1mm high thermal conductivity silicone layer (the matrix of the silicone is polymethyltriethoxysilane), a 1mm SG-0 type polyvinyl chloride layer, a 0.3mm aluminum alloy armor layer, a 1mm SG-4 type polyvinyl chloride layer, and a 0.05mm silicone grease coating are sequentially arranged on the surface of the 1mm first heat dissipation coating to obtain a high thermal conductivity flexible busbar.

[0054] Example 2

[0055] a. Ultrasonic dispersion of 5 parts of nano graphite powder and 0.2 parts of polyvinyl pyrrolidone, the power of ultrasonic dispersion is 300W, the time is 30min, add 8 parts of nano alumina powder, 1 part of aluminum nitride powder, 6 parts of silicon dioxide powder, 0.1 parts of silver powder, and then add 1 part of barium stearate dispersant, continue stirring and ultrasonic dispersion. Among them, the amount of anhydrous ethanol added is 5wt% to 20wt% of the weight of the powder. Then vacuum dry at 80℃, use a ball mill for 3 to 6 hours to filter, so that the particle size is less than 10μm, to obtain the first mixture;

[0056] b. 10 parts of epoxy resin and 1 part of polyethersulfone resin were first mixed with the first mixture, the mixing temperature was controlled at 90 ° C, the mixing time was 2 hours, and then 1 part of γ-aminopropyl triethoxysilane was added to the mixed product for a second mixing at 115 ° C. After the mixing was completed, the product was coated on a copper bus and cured in an oven at 350 ° C.

[0057] c. A 1mm high thermal conductivity silicone layer (the matrix of the silicone is polymethyltriethoxysilane), a 1mm SG-0 type polyvinyl chloride layer, a 0.3mm aluminum alloy armor layer, a 1mm SG-4 type polyvinyl chloride layer, and a 0.05mm silicone grease coating are sequentially arranged on the surface of the 1mm first heat dissipation coating to obtain a high thermal conductivity flexible busbar.

[0058] Example 3

[0059] a. Ultrasonic dispersion of 2 parts of nano graphite powder and 0.2 parts of polyvinyl pyrrolidone, the power of ultrasonic dispersion is 300W, the time is 30min, add 10 parts of nano alumina powder, 1 part of aluminum nitride powder, 5 parts of silicon dioxide powder, 0.1 parts of silver powder, and then add 0.5 parts of barium stearate dispersant, continue stirring and ultrasonic dispersion. Among them, the amount of anhydrous ethanol added is 5wt% to 20wt% of the weight of the powder. Then vacuum dry at 80℃, use a ball mill for 3 to 6 hours to filter, so that the particle size is less than 10μm, to obtain the first mixture;

[0060] b. 15 parts of epoxy resin and 3 parts of polyethersulfone resin are mixed with the first mixture for the first time, the mixing temperature can be controlled at 90 ° C, the mixing time is 2 hours, and then 3 parts of γ-aminopropyltriethoxysilane are added to the mixed product for the second mixing at 115 ° C. After the mixing is completed, the product is coated on the copper bus and cured in an oven at 350 ° C to obtain a nano-graphene composite ceramic coating;

[0061] c. A 1mm high thermal conductivity silicone layer (the matrix of the silicone is polymethyltriethoxysilane), a 1mm SG-0 polyvinyl chloride layer, a 0.3mm aluminum alloy armor layer, a 1mm SG-4 polyvinyl chloride layer, and a 0.05mm silicone grease coating are sequentially arranged on the surface of the 1mm nano-graphene composite ceramic coating to obtain a high thermal conductivity flexible busbar.

[0062] Comparative Example 1

[0063] In Comparative Example 1, no nano-graphene composite ceramic coating is provided on the copper busbar, and the rest is referred to Example 1.

[0064] Comparative Example 2

[0065] In step c of comparative example 2, a 1 mm high thermal conductivity silicone layer, a 0.5 mm SG-0 type polyvinyl chloride layer, a 0.1 mm aluminum alloy armor layer, a 0.5 mm SG-4 type polyvinyl chloride layer, and a 0.1 mm silicone grease coating are sequentially arranged on the surface of the 2 mm nano-graphene composite ceramic coating to obtain a high thermal conductivity flexible busbar. The rest refers to Example 1.

[0066] Performance Test:

[0067] The busbars obtained in the embodiments and comparative examples were tested for thermal conductivity, volume resistivity, tensile strength and elongation at break. The tests were performed according to national standards GB / T 10295-2008, GB / T12706.2-2008, GB / T 1410-2006 and GB / T13022-1991, and the results were recorded:

[0068] Table 1: Test results of Examples 1 to 3 and Comparative Examples 1 to 2

[0069]

[0070] As can be seen from Table 1, the coating design of the high thermal conductivity flexible busbar in this scheme achieves excellent thermal conductivity and heat dissipation effects through the careful selection and layered arrangement of materials. The innermost layer of nano-graphene composite ceramic coating uses the ultra-high thermal conductivity of graphene to quickly conduct heat; the high thermal conductivity silicone layer not only provides an additional heat conduction path, but also increases the flexibility and mechanical protection of the busbar; the aluminum alloy armor layer provides mechanical strength for the overall structure while enhancing electromagnetic compatibility; the two layers of polyvinyl chloride provide insulation and chemical corrosion resistance, and the outermost silicone grease coating further optimizes heat dissipation to ensure that heat is effectively transferred to the outside world. The synergistic effect of this series of materials not only improves the thermal management efficiency of the busbar, but also enhances its adaptability and durability in various environments, thereby ensuring the reliability and efficiency of power transmission.

[0071] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present invention are all included in the technical scope of the present invention. In addition, without departing from the scope of the main purpose of the present invention, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present invention.

Claims

1. A high thermal conductivity flexible busbar, characterized in that: The high thermal conductivity flexible busbar comprises a copper bus and a coating layer, wherein the coating layer is sequentially composed of: a first heat dissipation coating layer, a wrapping layer, a first polyvinyl chloride layer, an aluminum alloy armor layer, a second polyvinyl chloride layer, and a second heat dissipation coating layer from the inside to the outside.

2. The high thermal conductivity flexible busbar according to claim 1, characterized in that: The first heat dissipation coating is a nano-graphene composite ceramic coating. The raw materials for preparing the nano-graphene composite ceramic coating include, by weight: 19 to 38 parts of thermal conductive heat dissipation powder, 0.1 to 3 parts of barium stearate dispersant, 0.1 to 0.2 parts of polyvinyl pyrrolidone, 12 to 15 parts of epoxy resin, 1 to 3 parts of polyether sulfone resin, and 1 to 5 parts of silane coupling agent.

3. The high thermal conductivity flexible busbar according to claim 2, characterized in that: In parts by weight, the thermally conductive and heat dissipating powder comprises: 2 to 5 parts of nano graphite powder, 6 to 10 parts of nano alumina powder, 1 to 5 parts of aluminum nitride powder, 5 to 10 parts of silicon dioxide powder, and 0.1 to 0.2 parts of silver powder.

4. The high thermal conductivity flexible busbar according to claim 2, characterized in that: The silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane or N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane.

5. The high thermal conductivity flexible busbar according to claim 1, characterized in that: The wrapping layer is a high thermal conductivity silica gel layer, and the matrix of the silica gel includes polydimethylsiloxane or polymethyltriethoxysilane.

6. The high thermal conductivity flexible busbar according to claim 1, characterized in that: The second heat dissipation coating is a silicone grease coating.

7. The high thermal conductivity flexible busbar according to claim 1, characterized in that: The thickness of the first heat dissipation layer is 0.5 mm to 1.5 mm. The thickness of the wrapping layer is 0.5 mm to 2 mm. The thickness of the first polyvinyl chloride layer is 0.5 mm to 1.5 mm. The thickness of the aluminum alloy armor layer is 0.1 mm to 0.5 mm. The thickness of the second polyvinyl chloride layer is 0.5 mm to 1.5 mm. The thickness of the second heat dissipation coating layer is 0.01 mm to 0.1 mm.

8. A method for preparing a busbar according to any one of claims 1 to 7, characterized in that: The following steps are involved: a: ultrasonically dispersing nano-graphite powder and polyvinyl pyrrolidone, adding the remaining thermal conductive and heat dissipating powder, barium stearate dispersant, and anhydrous ethanol, stirring, ultrasonically dispersing, vacuum drying, grinding, and filtering to obtain a first mixture; b: kneading the epoxy resin, polyethersulfone resin and the first mixture for the first time, then adding the silane coupling agent for the second kneading, coating the kneaded product on the copper bus, baking and curing, to obtain a nano-graphene composite ceramic coating, i.e., the first heat dissipation coating; c: a wrapping layer, a first polyvinyl chloride layer, an aluminum alloy armor layer, a second polyvinyl chloride layer, and a second heat dissipation coating layer are sequentially arranged on the surface of the first heat dissipation layer to obtain a high thermal conductivity flexible busbar.

9. The method for preparing a busbar according to claim 8, characterized in that: In step a, the vacuum drying temperature is 70° C. to 85° C., and the grinding fineness is such that the particle size is less than or equal to 10 μm.

10. The method for preparing a busbar according to claim 8, characterized in that: In step b, the temperature of the first banburying is 90°C to 110°C, the temperature of the second banburying is 110°C to 118°C, and the temperature of the baking is 280°C to 550°C.